959 OPTIMISING MEDICAL CARE IN OLDER EMERGENCY UROLOGY PATIENTS USING A GERIATRICIAN-LED PERI-OPERATIVE SERVICE. (14th June 2022) - Lam, R; Dhesi, J; Forsyth, E; Streeter, E; Kommu, S; Thomas, M; Meilak, C
Abstract: Introduction: Older and frail patients account for a large proportion of urology service use (Drch GW, Griebling TL., JAGS, 2003; 51: S355–8). Frail patients are at higher risk of complications and readmissions (Suskind A et al., BJUI, 2016; 117:836–42). Emergency patients may not be optimised before admission, leading to further increased risk and time restraints on care planning. Therefore, a geriatrician-led Perioperative Care for Older People Undergoing Surgery (POPS) service was established within the urology department at a District General Hospital to improve older emergency urology inpatients' outcomes. We reviewed the impact on medical management, readmissions, and care planning. Method: Retrospective documentation review of emergency urology patients aged over 65 admitted in the 3 months before the POPS service implementation, compared to those reviewed by POPS in the 3 months following. Median clinical frailty score of the POPS group was 6. The Comprehensive Geriatric Assessment based inpatient perioperative service was created using co-design and staff questionnaires were completed post-implementation. Results: 100% of staff (n = 26) would recommend POPS to other surgical wards and comments on improvements focused on expansion (9/15). Conclusion: The POPS service significantly improved the recognition and management of medical conditions and reduced medical readmissions. Increased end of life recognition and planning allowed patients' wishes to be acted on. This service was successfully implemented with high staff acceptance.